2010
DOI: 10.3928/08910162-20100416-01
|View full text |Cite
|
Sign up to set email alerts
|

Work Environment Stressors, Social Support, Anxiety, and Depression Among Secondary School Teachers

Abstract: Work environment stress, a salient health and safety issue for secondary school teachers, school administrators, parents, and students, was examined in 168 teachers from two urban and five suburban high schools. The purpose of this study was to examine relationships between ongoing and episodic stressors and anxiety and depression, as well as the extent to which anxiety and depression may be predicted by stressors and coworker and supervisor support. The Ongoing Stressor Scale (OSS) and the Episodic Stressor S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 38 publications
2
33
0
8
Order By: Relevance
“…In an examination of teachers, Mahan et al. () measured various workplace factors such as stressors, social support from other coworkers and management, as well as anxiety and depression. They found that ongoing stressors as well as lack of coworker support were both significant in predicting depression and anxiety.…”
mentioning
confidence: 99%
“…In an examination of teachers, Mahan et al. () measured various workplace factors such as stressors, social support from other coworkers and management, as well as anxiety and depression. They found that ongoing stressors as well as lack of coworker support were both significant in predicting depression and anxiety.…”
mentioning
confidence: 99%
“…This clinical support is likely crucial in guarding against secondary traumatic stress in teachers. This support system is essential because teachers may not have enough opportunities for support outside of potential evaluation contexts (i.e., administrators) (Mahan et al., ). Ongoing feedback from consultants has also been linked to sustainability of school‐based interventions (Han & Weiss, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ponadto autorzy badań zaobserwowali, że ponad połowa respondentów odczuwała trudności związane z działalnością badawczą na uniwersytetach oraz wskazywała niekorzystny wpływ podejmowania przez nich dodatkowej pracy zarobkowej na ich osiągnięcia naukowo-dydaktyczne. 32 Sloane P.J., Ward E.W. : Cohort effects and job satisfaction of academics.…”
Section: Badania Satysfakcji Polskich Naukowcówunclassified
“…Jeszcze inne badania 32 wskazują na to, że mężczyźni poniżej 36. roku życia wykazują większe zadowolenie z pracy niż kobiety, natomiast po przekroczeniu tej granicy wiekowej proporcje te się zmieniają.…”
unclassified